Wild Sugarcane - Saccharum sp. germplasm collection in the states of Punjab and Haryana, India - Subramanian Karthigeyan; Perumal Govindaraj; Adhini S Pazhany (Journal of Sugarcane Research, 2021)
The Indian sub-continent harbours a great wealth of diversity of Saccharum and its related genera. Several targeted expeditions were conducted to collect the range of diversity present in Saccharum complex from diverse parts of the country. But the north western states of Punjab and Haryana were hitherto unexplored. A targeted exploration was conducted during 2016 to collect the entire range of variability present in Saccharum complex. Collections were made from a wide range of habitats and altitudes. The Saccharum spontaneum was present mostly along the river banks and river beds and showed considerable variability for morphological characteristics. S. spontaneum was distributed throughout both the states and collections could be made from all the districts and union territory of Chandigarh. A total of 104 accessions comprising of 100 Saccharum spontaneum and four Erinathus sp. have been collected. They were occurring mostly as small population except in the canal bunds where larger population was noticed. Plant height ranged from 0.46 m to 4.5 m. Variation for leaf and stem characters were observed from the collections. Statistical analysis of altitude of the collection sites with plant characters showed no significant association. Correlation analysis among plant characters showed the highest correlation coefficient between plant height and internode thickness. Clustering of Haryana, Chandigarh and Punjab Saccharum spontaneum collections through complete linkage clustering resulted in five clear clusters among the collections. Geographic distance and environmental factors including local climates interplay in the formation of the genetic structure and geographic patterns of the native S. spontaneum populations. Haryana and Punjab state were not much explored during earlier period and hence the collection would add more diversity to the germplasm maintained. In addition to the 100 S. spontaneum, four Erianthus sp. were collected during the exploration which will enrich the gene pool.